Factors Causing Low Participation of Natural Parents Stimulates the Ability of Early Reading of Children Natural Family - Ismaniar, Ismaniar; Jamaris, Jamaris; Wisroni, Wisroni (Universitas Negeri Semarang, 2019)
The background of this research is due to the phenomenon of not yet developing early reading skills in children. The purpose of this study is to find out factors that caused the lack of parental participation in stimulating The ability to read early children in families in the city of Padang. This study is descriptive quantitative study. The sample of this study is parents who have children aged 4-5 years old who live in Padang city. There are 20 people. Taking sample is used purposive random sampling techniques, that is parents of children who show symptoms of underdeveloped early reading skills. Data Collection uses interview techniques, with interview guidance tools, while for Data processing researchers use a percentage formula. The result of this study is that there were three dominant factors that led to a lack of parental participation in stimulating children’s early reading abilities, there are (1) Parent’ s lack understanding about the tasks and Functional of Paud institutions, (2) The limited time that parents have because they are must work to meet the family’s economic needs, (3) Limited sharing and characteristics of parents about The characteristic and learning styles of early childhood.